Antifungal activity of alexidine dihydrochloride in a novel diabetic mouse model of dermatophytosis - Nabeela, Sunna; Date, Abhijit; Ibrahim, Ashraf S.; Uppuluri, Priya (Frontiers in Cellular and Infection Microbiology, 2022)
Dermatophytosis is one of the most prevalent fungal infections and a major public health problem worldwide. Recent years have seen a change in the epidemiological patterns of infecting fungi, corresponding to an alarming rise in the prevalence of drug-recalcitrant dermatophyte infections. In patients with diabetes mellitus, dermatophytosis is more severe and recurrent. The potency of promising new antifungal drugs in the pipeline must be expanded to include dermatophytosis. To facilitate this effort, we established a clinically pertinent mouse model of dermatophyte infections, in which diabetic mice were infected with Trichophyton mentagrophytes on abraded skin. The diabetic mouse model was optimized as a simple and robust system for simulating dermatophytoses in diabetic patients. The outcome of infection was measured using clinical and mycological parameters. Infected mice with fungal lesions were treated with oral and topical formulations of terbinafine or topical administration of the FDA-approved and repurposed pan-antifungal drug alexidine dihydrochloride (AXD). In this model, AXD was found to be highly effective, with outcomes comparable to those of the standard of care drug terbinafine.